Cover Picture: Dzyaloshinskii–Moriya interactions and magnetic texture in Fe films deposited on transition‐metal dichalcogenides (Phys. Status Solidi RRL 3/2016). Issue 3 (March 2016) - Polesya, S.; Mankovsky, S.; Ködderitzsch, D.; Bensch, W.; Ebert, H.
Abstract : No abstract is available for this article. Abstract : Magnetic skyrmions attract much attention for various spintronic applications as the topologically protected magnetic texture with particle‐like behaviour can be easily manipulated using relatively low electric current densities. Deposited ultra‐thin magnetic films are considered as a promising class of materials for which stable skyrmions can be created. The work by Polesya et al. (pp.218–221 ) is devoted to the investigation of an Fe monolayer on a transition‐metal dichalcogenide substrate. These films exhibit rather strong ferromagnetic interactions as well as strong anisotropic Dzyaloshinskii–Moriya interactions. The corresponding coupling parameters can be easily tuned by varying the composition of the substrate. This makes this system attractive for practical applications.